The Effects of Resistance and Aerobic Exercise Sequence on Energy Expenditure - Schoenike, Keisha; Haller, Jessica; LaRocque, Brittany (My University, 2011)
There has been little research to determine the optimal order of aerobic and resistance exercise with respect to the amount of calories expended, which may provide a rationale for considering the sequence of exercise when designing exercise programs. This study examines the effects of exercise sequence on energy expenditure during a single exercise bout.
Color poster with text, photographs, charts, and graphs.
Keywords: Physical fitness--Measurement; Posters; Exercise--Physiological aspects--Research; Exercise--Planning